2022
DOI: 10.1097/mco.0000000000000874
|View full text |Cite
|
Sign up to set email alerts
|

Diet and the microbiota–gut–brain-axis: a primer for clinical nutrition

Abstract: Purpose of reviewDiet is an essential modulator of the microbiota–gut–brain communication in health and disease. Consequently, diet-induced microbiome states can impact brain health and behaviour. The integration of microbiome into clinical nutrition perspectives of brain health is sparse. This review will thus focus on emerging evidence of microbiome-targeted dietary approaches with the potential to improve brain disorders.Recent findingsResearch in this field is evolving toward randomized controlled trials u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…While the mechanisms linking MS-diet to depression are uncertain, a role of the gut-brain axis has been suggested (27). Inflammation is known to play a key role in MS progression (46) and the anti-inflammatory and neuroprotective effects of fruit/vegetables and of low saturated fat diet have been documented (9,47,48). Our findings may be in part explained by the anti-inflammatory effects of a low saturated fat diet such as the OMS-diet.…”
Section: Discussionmentioning
confidence: 50%
“…While the mechanisms linking MS-diet to depression are uncertain, a role of the gut-brain axis has been suggested (27). Inflammation is known to play a key role in MS progression (46) and the anti-inflammatory and neuroprotective effects of fruit/vegetables and of low saturated fat diet have been documented (9,47,48). Our findings may be in part explained by the anti-inflammatory effects of a low saturated fat diet such as the OMS-diet.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, new clinical trials indicated that the gut-microbiota–brain axis pathways and mechanisms are prone to dietary modulation and are of vital interest in clinical nutrition. As a matter of fact, dietary interventions and supplementation with probiotics and prebiotics can reshape the bacterial composition and are now administered as “psychobiotics” to treat neurological disorders because of their beneficial effects on the brain [ 176 ]. This means that by reshaping the GM, the whole gut-microbiota-BBB axis is positively modulated.…”
Section: Beneficial Modulation Of the Gut-microbiota–brain Axismentioning
confidence: 99%
“…The Mediterranean diet constitutes a food model that characterizes not only a lifestyle but also a culture and has been indicated as a hub for improving health, quality of life, and life span. Numerous studies have highlighted the positive correlation between MD and longevity; individuals who adhere to a nutritional style such as this have a longer life expectancy [ 81 , 82 ]. Moreover, the Mediterranean diet prevents many metabolic, cardiovascular, and neurodegenerative diseases; insulin resistance; and different types of cancer [ 83 , 84 ].…”
Section: The Mediterranean Diet (Md)mentioning
confidence: 99%